Exploring notions of community in a privately owned early childhood education and care centre in New Zealand. Issue 2 (14th March 2020) - Hamer, Judy; Loveridge, Judith
Abstract: There has been increasing debate about the role early childhood education and care (ECEC) plays within local and wider communities. This article reports on a small-scale case study that explored the views of teachers, management and parents from a privately owned ECEC centre in New Zealand about the notion of community. Rogoff's planes of sociocultural activity have been used as the theoretical framework for generating and analysing data. Findings highlight that while the business model of this centre shaped its orientation to community, the participants expressed diverse views about community, emphasising the importance of connections between people and place both within and beyond the centre. We argue that viewing the ECEC setting as an extended family rather than a community may afford greater recognition of broader emotional and social benefits of participating in ECEC for children, their families and society as a whole.